2020
DOI: 10.21608/ajbas.2020.23319.1009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial quality of Oreochromis niloticus samples of Lake Manzala, Egypt

Abstract: The present study aimed to investigate bacterial quality of tilapia fish (Oreochromis niloticus) and evaluate the hygienic health hazard of fish contaminated with some food borne pathogens. Bacteria were isolated from intestine, gills and flesh of Oreochromis niloticus collected from Lake Manzala during two seasons; winter and summer, 2017. Microbiological studies was applied for all samples as total viable bacteria, total coliform, faecal coliform, faecal streptococcus and examined for the presence of Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Most previous studies showed that the lowest numbers of the bacterial indicators were recorded at sites opposite the Boghazes (which feed the lake with saline water from the Mediterranean Sea), whereas the greatest bacterial indicators were found mostly at the sites close to the discharge points of polluted and untreated water via the drains. This data interpretation agrees with the results obtained by Tahoun (2016), Ibrahim (2017), andEl-ghannam et al (2020).…”
Section: Fig 3: Biochemical Contents Of Phytoplankton In Lake Manzalasupporting
confidence: 93%
“…Most previous studies showed that the lowest numbers of the bacterial indicators were recorded at sites opposite the Boghazes (which feed the lake with saline water from the Mediterranean Sea), whereas the greatest bacterial indicators were found mostly at the sites close to the discharge points of polluted and untreated water via the drains. This data interpretation agrees with the results obtained by Tahoun (2016), Ibrahim (2017), andEl-ghannam et al (2020).…”
Section: Fig 3: Biochemical Contents Of Phytoplankton In Lake Manzalasupporting
confidence: 93%
“…Catalase test was carried out by using a small number of bacteria collected from a fresh-isolated 18-24 hour colony to a drop of 3% H 2 O 2 . Catalase positive results are evident by immediate effervescence and bubbles formation of O 2 [36] [37]. A single pure colony from a freshly isolated bacterial culture was taken up and slowly mixed in droplets of distilled water for the Oxidase Test.…”
Section: Purification and Identificationmentioning
confidence: 99%